Metabolic assessment of cerebral palsy with normal clinical MRI using 18F-FDG PET imaging: A preliminary report - Wu, Ruimin; Gao, Yan; Zhang, Huaqiong; Chen, Yijia; Tan, Fan; Zeng, Daobing; Wan, Huabing; Yang, Yi; Gu, Jiaowei; Pei, Zhijun (Frontiers in Neurology, 2022)
To explore the cerebral metabolic patterns of cerebral palsy (CP) patients without structural abnormalities by brain magnetic resonance imaging (MRI) scans, we evaluated 18F-fluoro-deoxyglucose positron emission tomography (18F-FDG PET) imaging features in patients. Thirty-one children with CP (Gross Motor Function Classification System (GMFCS) levels II-V) showing no structural abnormalities by MRI were enrolled in this study. Regional glucose metabolic activity values were calculated using Scenium software and compared between the right and left cerebral hemispheres. These comparisons revealed asymmetric metabolic reductions in the central region, cerebellum, frontal lobe, and parietal lobe (p < 0.01). We next determined whether averaged brain metabolic activity values in different brain regions correlated with GMFCS levels. The metabolic activity values of basal ganglia, left temporal lobe, and cerebellum correlated negatively with GMFCS scores (all p < 0.05). This method was applied to the left cerebellum, which showed higher metabolic activity values than those in the right cerebellum in most patients (83.8%), and these values also correlated negatively with GMFCS scores (Spearman’s r = -0.36, p = 0.01). Differential cortical glucose metabolism by 18F-FDG PET, may help to distinguish between different CP diagnoses that are not detected by MRI.